Send me an update - Mackey, Daphne (McGraw-Hill, 2006)
With the expansion of global business and the strong role that English plays in it, communicating clearly in written English has become essential for business people around the world. Send Me A Message and Send Me An Update guide students to proficiency in both the use of the language and in the various formats of business writing